The Outside : Migration as Life in Morocco - Elliot, Alice (Social anthropologist) (Book collections on Project MUSE., 2021)
"The Outside: Migration as Life in Morocco traces how migration has come to occupy a striking place in the lives of many Moroccans. A full 10 percent of the population now lives outside the country, affecting individual and collective life in countless unanticipated ways. In this intimate ethnography of rural Morocco, Alice Elliot considers the experience of migration from the point of view of the families and people, mostly women, who have not (yet) left. Elliot shows how the specter of migration has permeated life, from kinship relations to intimacy between spouses and to the imagination of the future. The Outside seeks to answer the question, what is migration when it becomes the very foundation on which forms of social and individual life are built? New understandings of migration emerge through its intimate textures as Elliot shows how it has become, in some parts of the world, a distinctive condition of everyday life"--